Creating new technology for student preparation towards IR4.0 - Nur Sa’adatul Afzan, Jusoh (2019)
Since the advent of the Fourth Industrial Revolution (IR 4.0) in the mid-2016 with automation technology, new challenges have emerged in all of the country's service and industrial sectors. It demands a change in all aspects of digital transformation to remain competitive and accelerate the progress of the modern world, as it will have a direct impact on the future of the current working environment.